Computational analysis of cyclonic separation - Sasan, Salour. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2014., 2014)
Cyclonic separation is a method to remove particles from a uid ow using a vortex for separation. This method of separation can be used to separate ne droplets of liquid or particles from a gas ow. This device is a kind of stationary mechanical device that uses centrifugal force to separate any kind of particles from a uid stream. There are two fundamental types of air cyclones according to the direction in which the cleaned gas leaves the cyclone. The reverse ow cyclone is one of them and it is actually the most frequently used type in industry. While the clean gas leaves from upper lid, separated particles can exit through a bottom apex. Cyclones have simple manufacturing, low energy requirements, capability to work at high pressures and temperatures. In spite of the simplicity in manufacturing and operation, the mathematical formulations used for anticipating the separation e ciency are very complicated. In contrast to most of the previous studies which use a single input, in this study two slot type cyclone separators are considered and compared together, for both laminar and turbulent ows. In this research, mathematical modeling of cyclonic separation is based on Muschelknautz Method formulation (MM) and the computational uid dynamics (CFD) analysis is performed using the COMSOL Multi-Physics program. Some of the well-known models such as Muschelknautz D type, Swift High E ciency, Stairmand High E ciency and Lapple General Purpose with single and double inputs are analyzed and compared. A model with di erent input sizes with single and double inputs is introduced and parameterized in terms of pressure drop pro le, velocity magnitude, number of particles that each cyclone can separate, separation e ciency and stream lines in laminar and turbulent streams. The particle tracing module of COMSOL is used for that purpose.
Keywords: Particles.